Preliminary Ruling Procedure in Serbian Civil Litigation : The Subject and its Characteristics - Jokić, Olivera (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The preliminary ruling procedure in Serbian civil litigation is initiated ex officio by the first-instance court during an ongoing proceeding. This process requires the Supreme Court to interpret legal rules or address legal gaps to ensure uniformity of case law. For such a ruling procedure to be justified, the specific legal issue must arise in a significant number of cases. However, the Supreme Court’s case law regarding interpreting this legal standard is divergent. Therefore, one of the tasks of this paper is to determine that legal standard. The central focus of this paper is the subject matter of the procedure — the disputable or "unresolved" legal issue — and its characteristics. Various positions are taken in the doctrine regarding these issues, while the Supreme Court’s case law remains inconsistent. As a result, the paper examines two theses: 1) the disputable legal issue is neither a preliminary nor a prejudicial question, and 2) it can be both substantive and procedural.